2021
DOI: 10.1007/s12088-021-00948-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Stress on Gut Microbiome in Rats

Abstract: Gut microbiome, as the largest and most important micro-ecosystem, plays a critical role in health. The purpose of this study was to evaluate whether heat stress modulates the composition and diversity of the gut microbiome in rats. The heat stress model was prepared in rats with the heating temperature maintained at 35–38°C. Cecum contents were collected after heat stress for 3 h and days 1, 3 and 7. Total DNA was extracted for 16 S rRNA sequencing and analysis of intestinal microbiome composition and diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
3
12
0
1
Order By: Relevance
“…( 228 ) found that heat stress increased the relative abundance of Firmicutes , Tenericutes , and Proteobacteria in the intestines of broilers, but decreased the relative abundance of Bacteroidetes and Cyanobacteria ; Qu et al. ( 229 ) found that heat stress increased the relative abundance of Oscillospira and Clostridium in murine intestines, but decreased the relative abundance of Lactobacillus and Bacteroides . Study have showed that the Lactobacillus was positively associated with serum total antioxidant, while some other microbial species were found negatively associated, such as Pseudomonadales and Acinetobacter ( 230 ).…”
Section: Dietary Supplementation Of Se To Increase Nutrient Digestibility and Regulate The Gastrointestinal Microbiome Of Heat Stressed Lmentioning
confidence: 99%
“…( 228 ) found that heat stress increased the relative abundance of Firmicutes , Tenericutes , and Proteobacteria in the intestines of broilers, but decreased the relative abundance of Bacteroidetes and Cyanobacteria ; Qu et al. ( 229 ) found that heat stress increased the relative abundance of Oscillospira and Clostridium in murine intestines, but decreased the relative abundance of Lactobacillus and Bacteroides . Study have showed that the Lactobacillus was positively associated with serum total antioxidant, while some other microbial species were found negatively associated, such as Pseudomonadales and Acinetobacter ( 230 ).…”
Section: Dietary Supplementation Of Se To Increase Nutrient Digestibility and Regulate The Gastrointestinal Microbiome Of Heat Stressed Lmentioning
confidence: 99%
“…Heat stress is the most serious stress that causes adverse effects on growth performance, immunity, mortality, and breast meat quality (1)(2)(3)(4). Emerging evidence demonstrates that heat stress can aggravate metabolic disorders and intestinal diseases (5)(6)(7)(8)(9)(10). Based on our previous study, we found that heat stress has a critical impact on the composition of gut microbiota, growth performance, circulating levels of HSP70, and cortisol (11).…”
Section: Introductionmentioning
confidence: 82%
“…Heat-stress experiments in rats allow for easier control of experimental conditions and shorter experimental times. Based on a preliminary exploration [ 46 ], this study selected conditions of 42 °C, 50% RH (THI = 93.96) for 120 min with the strongest heat stress performance in order to simulate the physiological response state of rats under short-term, non-extreme lethal heat stress conditions [ 47 , 48 , 49 ]. In livestock production, the daily RH of the farm is constantly changing, and THI can more easily quantify the degree of heat stress experienced by herds.…”
Section: Discussionmentioning
confidence: 99%